Bilateral conjunctival sporotrichosis in a domestic cat: case report - Silva, Joelson Cavalcanti; de Freitas Silva, Gabriella Menezes; Carvalho, Lucas Rannier Ribeiro Antonino (Frontiers in Veterinary Science, 2025)
Feline sporotrichosis is a subcutaneous mycosis caused by the dimorphic fungi of the genus Sporothrix. It is a zoonotic disease that has been increasingly reported in Brazil. While it commonly presents as skin nodules, nasal discharge, and generalized ulcerative lesions, ocular involvement is rare. This case report describes an unusual presentation of sporotrichosis with bilateral conjunctival manifestations in a 2-month-old domestic mixed-breed kitten treated at a private veterinary hospital in João Pessoa. Clinical examination revealed hyperemic conjunctivae with a granulomatous appearance, follicles, chemosis, and mucopurulent secretion. Additional tests were requested, including complete blood count, tests for feline immunodeficiency virus (FIV) and feline leukemia virus (FeLV), antibiogram, fungal culture, and exfoliative cytology. The antibiogram identified Enterococcus sp., sensitive only to 10 μg gentamicin, and cytology revealed yeasts consistent with Sporothrix spp., which was subsequently confirmed by fungal culture. Treatment was adjusted with gentamicin eye drops, topical and oral itraconazole, hepatoprotector and a food supplement containing beta-glucans to aid healing. After 1 month of therapy, the lesions disappeared, leaving the only sequelae as adhesion of the third eyelid to the palpebral conjunctiva. Ocular sporotrichosis in kittens is a rare condition and, in this case, bilateral involvement was observed, which suggests the need to consider this disease in the differential diagnosis of cats with ophthalmic alterations, especially in urban environments with a high prevalence of the disease. Treatment began with oral itraconazole and topical adjuvant therapy, resulting in clinical remission after 4 months of treatment.